Pedagogical Projection of María Luisa Navarro and Isabel Luzuriaga in the republican exile - Diamant, Ana; Bejarano Franco, María Teresa (Historia y Memoria de la Educación, 2019)
The purpose of this article is to show the biography and the career path of two republican women who shared an unforgettable experience in the context of the Spanish exile (1936). Together with their filial ties ― they were mother and daughter ― Mª Luisa Navarro and Isabel Luzuriaga shared a common concern for childhood, education and learning difficulties. . Mª Luisa was part of the group of women whose work contributed to significant improvements in Spanish society and to the modernization of the education system. She collaborated with the Misiones Pedagógicas, the education for blind and visually-impaired people, and in support of women´s rights, which she managed to work for in her time spent in exile. . Isabel went to Argentina as a child after having lived for several years in the United Kingdom, the country she would return to during her professional career. She focused on child psychoanalysis and she was the first teacher of this subject in Psychological Studies at the University of Buenos Aires. She had a second exile in 1976 in Spain, her native country, where she lived until her death . The objective of this article is to reveal the academic contributions that both figures made from Pedagogy and Psychology, taking into account contextual, political and exile-related variables. Despite both women’s contributions to education and teaching, from a Pedagogical and Psychological point of view and with contextual variables, they never achieved broad recognition either as professionals or as women’s activists. This study shines a spotlight on these two women by examining their work and by resorting to several personal oral testimonies. These include that of Isabel Luzuriaga, and of many people who lived and worked closely with them.